Rekonfigurasi Pengawasan Peradilan di Indonesia: Komisi Yudisial dan Batasan Konstitusional dalam Penegakan Integritas Hakim - Karisa Parameswary; Denie Amiruddin; Immada Ichsani; Hendayana Hendayana (Society, 2025)
Judicial integrity constitutes a fundamental pillar of the rule of law and democratic governance. In Indonesia’s post-1998 reform era, the establishment of the Judicial Commission (Komisi Yudisial) was intended to strengthen external oversight of judicial conduct and enhance public trust in the judiciary. However, the effectiveness of this institution has been significantly constrained by Constitutional Court Decision No. 005/PUU-IV/2006, which limited the Commission’s authority in supervising judges, particularly those within the Supreme Court. This article examines how these constitutional limitations affect the effectiveness of judicial oversight and the broader framework of judicial accountability in Indonesia. The study employs a normative juridical method, focusing on the analysis of constitutional provisions, statutory regulations, and judicial decisions governing the authority of the Judicial Commission. Legal doctrines on the hierarchy of norms and the theory of separation of powers are used to evaluate the consistency of existing regulations with the constitutional mandate under Article 24B of the 1945 Constitution. The findings indicate that the Constitutional Court’s interpretation has fragmented the judicial oversight system, weakened external accountability, and created structural imbalances within the system of checks and balances. To address these challenges, the article proposes constitutional and institutional reforms aimed at strengthening the Judicial Commission’s authority, enhancing transparency, and restoring public confidence in the judiciary. Such reforms are essential to ensure that judicial independence is accompanied by effective mechanisms of accountability.